Advanced Air Mobility: Transcending the Frontiers of Aviation Law (Frontiers in Law, 2024)
This article examines the revolutionary concept of Advanced Air Mobility (AAM) and its potential to transform urban and regional transportation. It begins by contextualizing AAM within the broader trajectory of aviation advancements, showcasing its emergence as a cutting-edge solution for modern transportation challenges. The discussion highlights the defining characteristics of AAM, such as its reliance on autonomous aircraft, electric propulsion technologies, and seamless integration with existing transit systems.The United States’ leadership in this sector is explored, with an emphasis on federal initiatives, partnerships between public and private entities, and the regulatory role of the Federal Aviation Administration. The article identifies key challenges that must be addressed to realize AAM's potential, including technological hurdles, public trust, and the intricacies of managing congested urban airspaces.Further analysis underscores the significant benefits AAM offers, such as reducing traffic congestion, enhancing accessibility, and promoting environmentally sustainable solutions. The article also delves into the legal and regulatory frameworks governing AAM, identifying critical areas that demand reform, such as liability, certification processes, and safety standards. By addressing these issues, the aviation sector can ensure that AAM evolves responsibly, meeting societal needs while adhering to essential legal principles.